Autopsy confirmed multiple system atrophy cases: Mayo experience and role of autonomic function tests. Issue 4 (6th January 2012) - Iodice, Valeria; Lipp, Axel; Ahlskog, J Eric; Sandroni, Paola; Fealey, Robert D; Parisi, Joseph E; Matsumoto, Joseph Y; Benarroch, Eduardo E; Kimpinski, Kurt; Singer, Wolfgang; Gehrking, Tonette L; Gehrking, Jade A; et al.
Abstract : Background: Multiple system atrophy (MSA) is a sporadic progressive neurodegenerative disorder characterised by autonomic failure, manifested as orthostatic hypotension or urogenital dysfunction, with combinations of parkinsonism that is poorly responsive to levodopa, cerebellar ataxia and corticospinal dysfunction. Published autopsy confirmed cases have provided reasonable neurological characterisation but have lacked adequate autonomic function testing. Objectives: To retrospectively evaluate if the autonomic characterisation of MSA is accurate in autopsy confirmed MSA and if consensus criteria are validated by autopsy confirmation. Methods: 29 autopsy confirmed cases of MSA evaluated at the Mayo Clinic who had undergone formalised autonomic testing, including adrenergic, sudomotor and cardiovagal functions and Thermoregulatory Sweat Test (TST), from which the Composite Autonomic Severity Score (CASS) was derived, were included in the study. Results: Patient characteristics: 17 men, 12 women; age of onset 57±8.1 years; disease duration to death 6.5±3.3 years; first symptom autonomic in 18, parkinsonism in seven and cerebellar in two. Clinical phenotype at first visit was MSA-P (predominant parkinsonism) in 18, MSA-C (predominant cerebellar involvement) in eight, pure autonomic failure in two and Parkinson's disease in one. Clinical diagnosis at last visit was MSA for 28 cases. Autonomic failure was severe: CASS was 7.2±2.3 (maximum 10). TST% was 65.6±33.9% and exceeded 30% in 82% of patients. The most common pattern was global anhidrosis. Norepinephrine was normal supine (203.6±112.7) but orthostatic increment of 33.5±23.2% was reduced. Four clinical features (rapid progression, early postural instability, poor levodopa responsiveness and symmetric involvement) were common. Conclusion: The pattern of severe and progressive generalised autonomic failure with severe adrenergic and sudomotor failure combined with the clinical phenotype is highly predictive of MSA.